The Discs Structures of A4-Graph for the Held Group - Al-Adhami, Asawer; Majeed, Aliaa. Aqeel; Aubad, Ali Abd (Iraqi Journal of Science, 2022)
Let G be a finite group and X be a G-conjugacy of elements of order 3. The A4-graph of G is a simple graph with vertex set X and two vertices x,yÎX are linked if x≠ y and xy-1 is an involution element. This paper aims to investigate  the A4-graph properties for the monster  Held group He.